Cholesterol‐α‐glucosyltransferase gene is present in most Helicobacter species including gastric non‐Helicobacter pylori helicobacters obtained from Japanese patients. Issue 1 (7th November 2017) - Kawakubo, Masatomo; Horiuchi, Kazuki; Matsumoto, Takehisa; Nakayama, Jun; Akamatsu, Taiji; Katsuyama, Tsutomu; Ota, Hiroyoshi; Sagara, Junji
Abstract: Background: Non‐ Helicobacter pylori helicobacters (NHPHs) besides H. pylori infect human stomachs and cause chronic gastritis and mucosa‐associated lymphoid tissue lymphoma. Cholesteryl‐α‐glucosides have been identified as unique glycolipids present in H. pylori and some Helicobacter species. Cholesterol‐α‐glucosyltransferase (αCgT), a key enzyme for the biosynthesis of cholesteryl‐α‐glucosides, plays crucial roles in the pathogenicity of H. pylori . Therefore, it is important to examine αCgTs of NHPHs. Materials and Methods: Six gastric NHPHs were isolated from Japanese patients and maintained in mouse stomachs. The α CgT genes were amplified by PCR and inverse PCR. We retrieved the α CgT genes of other Helicobacter species by BLAST searches in GenBank. Results: α CgT genes were present in most Helicobacter species and in all Japanese isolates examined. However, we could find no candidate gene for αCgT in the whole genome of Helicobacter cinaedi and several enterohepatic species. Phylogenic analysis demonstrated that the α CgT genes of all Japanese isolates show high similarities to that of a zoonotic group of gastric NHPHs including Helicobacter suis, Helicobacter heilmannii, and Helicobacter ailurogastricus . Of 6 Japanese isolates, the α CgT genes of 4 isolates were identical to that of H. suis, and that of another 2 isolates were similar to that of H. heilmannii and H. ailurogastricus . Conclusions: All gastric NHPHs examined showed presence of α CgT genes, indicating that αCgT may be beneficial for these helicobacters to infect human and possibly animal stomachs. Our study indicated that NHPHs could be classified into 2 groups, NHPHs with α CgT genes and NHPHs without α CgT genes.